IL-23/IL-17 Axis Activates IL-1β-Associated Inflammasome in Macrophages and Generates an Auto-Inflammatory Response in a Subgroup of Patients With Bullous Pemphigoid - Le Jan, Sébastien; Muller, Céline; Plee, Julie; Durlach, Anne; Bernard, Philippe; Antonicelli, Frank (Frontiers in Immunology, 2019)
Bullous Pemphigoid (BP) is a skin autoimmune blistering disease characterized by immune-mediated degradation of the dermo-epidermal junction and release of a large number of inflammatory cytokines. Interleukin-1β (IL-1β) is a pleiotropic pro-inflammatory cytokine associated with inflammasome activation and known to be pivotal in several auto-immune and auto-inflammatory diseases. We sought to clarify the presence of inflammasome-dependent IL-1β and to investigate its role in BP. Skin biopsy specimens (n=13), serum (n=60), blister fluid (n=26) and primary inflammatory cells from patients with BP were used to investigate inflammasome activation and function. We here highlighted a differential occurrence of a functional in situ inflammasome in patients with BP, biologically distinguished by IL-1β and NLRP3 expression, Clinically, elevated IL-1β levels were associated to the presence of erythema and urticarial plaques reflecting the inflammatory phase preceding blister formation. We further identified IL-17 and IL-23 as important molecules favouring IL-1β expression in monocyte-derived macrophages from BP patients. Finally, we demonstrated the ability of IL-1β to stimulate the release of the matrix metalloproteinase-9 in those macrophages, reinforcing the role of IL-1β in the auto-amplification loop of the inflammatory response associated to BP. However, whether this inflammasome is an epiphenomenon associated with BP disease or constitutes an amplification inflammatory step in certain patients still need to be determined. In the context of a precision medicine approach, our findings allowed us delineating a subgroup of patients with BP that showed similarities with auto-inflammatory diseases. Subsequently, this opens up alternative therapeutic strategies targeting IL-1β pathway in the aim to control the early, pre-blistering inflammatory phase. Ultimately, this could also help in reducing the detrimental effects associated with high doses of corticosteroids treatment.